2010
DOI: 10.4314/njps.v22i1-2.54873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine -coconut products interactions on induction of microsomal drug-metabolizing enzymes in wistar albino rats

Abstract: Summary: Effect of caffeine-coconut products interactions on induction of drug-metabolizing enzyme in wistar albino rats was studied. Twenty rats were randomly divided into four groups: The control group (1) received via oral route a placebo (4.0ml of distilled water). Groups 2 to 4 were treated for a 14-day period with 50mg/kg body weight of caffeine, 50mg/kg body weight of caffeine and 50mg/kg body weight of coconut water, and 50mg/kg body weight of caffeine and 50mg/kg body weight of coconut milk in 4.0ml o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Akande and Banjoko (2011) revealed to disorders in kidney function in rats by treated with energy beverage and increasing of urea concentration , and this result agree with Otero-Losada et al (2013) who reported high urea after cola drinking . The result of the present study found a significant decreasing in liver enzymes (ALT,AST and ALP) which belong to effect of caffeine that present in carbonated beverages , Abara et al (2007) reported that caffeine has role in reduction activity of liver enzymes , This agree with Chen et al (2006) noted many side effects in hepatocytes resulted from caffeine . Significant increasing in glucose level of treated groups , this due to a large amount of carbohydrates in carbonated beverages which will be metabolize into glucose , Morengal et al (2012) found content carbohydrates in soft drinks and he refers to consumption of carbonated www.Jutq.utq.edu.iq Web Site of the Journal has also been associated with poor dietary habits , weight gain and type 2 diabetes, predominately in adults .…”
Section: Discussionsupporting
confidence: 89%
“…Akande and Banjoko (2011) revealed to disorders in kidney function in rats by treated with energy beverage and increasing of urea concentration , and this result agree with Otero-Losada et al (2013) who reported high urea after cola drinking . The result of the present study found a significant decreasing in liver enzymes (ALT,AST and ALP) which belong to effect of caffeine that present in carbonated beverages , Abara et al (2007) reported that caffeine has role in reduction activity of liver enzymes , This agree with Chen et al (2006) noted many side effects in hepatocytes resulted from caffeine . Significant increasing in glucose level of treated groups , this due to a large amount of carbohydrates in carbonated beverages which will be metabolize into glucose , Morengal et al (2012) found content carbohydrates in soft drinks and he refers to consumption of carbonated www.Jutq.utq.edu.iq Web Site of the Journal has also been associated with poor dietary habits , weight gain and type 2 diabetes, predominately in adults .…”
Section: Discussionsupporting
confidence: 89%
“…Regarded of liver enzymes, the current study revealed to significant decrease (P≤ 0.05) in liver enzymes (ALT, AST and ALP) in all groups treated with Puma super fat when compared with control group, this decline in enzymes was increased significantly (P≤0.05) as a result of elevated receiving of Puma (Super fat). That decrease may be due to presence of caffeine in Puma super fat, this accordance with Abara et al (2007) who found reduction of liver enzymes by caffeine. Also, this decline is identical with Kumar and Anandan (2007) who explained decreasing of ALT and AST by exposure for glutamin supplement, while that did not agree with Waldron et al (2002) who mentioned to administration of nutritional supplements led to high liver enzymes.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 86%
“…Metabolic derangement and subsequent toxicity of caffeine leads to weight loss, poor growth, low protein efficiency ratio and poor nitrogen retention, leading to death. 3,7 Thus, the toxicity of caffeine is viewed as a disposition demonstrating that caffeine is rapidly absorbed but slowly excreted. Caffeine also acts to increase alertness, anxiety and hallucination due to its blocking of adenosine receptors, [8][9][10] which normally inhibits glutamate release.…”
Section: Introductionmentioning
confidence: 99%